2013
DOI: 10.1590/s1516-89132013000200005
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the presence and type of fragrance on the sensory perception of cosmetic formulations

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 23 publications
0
16
0
5
Order By: Relevance
“…The main variance is explained by Factor 1 (66.81%) and Factor 2 (17.64%). The loading plot of the sensory variables presented in Figure 5 showed that the overall preference of the sun creams was significantly related to the textural characteristics (spreadability, penetration, softness, and skin feel) [55] and to the persistence of the odor in the skin [56].…”
Section: Sensory Analysismentioning
confidence: 99%
“…The main variance is explained by Factor 1 (66.81%) and Factor 2 (17.64%). The loading plot of the sensory variables presented in Figure 5 showed that the overall preference of the sun creams was significantly related to the textural characteristics (spreadability, penetration, softness, and skin feel) [55] and to the persistence of the odor in the skin [56].…”
Section: Sensory Analysismentioning
confidence: 99%
“…Hence, it seems that a significant interaction effect can only be expected between tactile stimuli and matching low-salient scents. Previous studies that did find crosssmodal interaction effects between olfaction and touch typically used naturalistic tactile stimuli like textile samples (Demattè et al, 2006;Guest & Spence, 2003b;Laird, 1932), cream and gels (Gonçalves et al, 2013;Kikuchi, Akita & Abe, 2013) or shampoo and hair (Churchill et al, 2009). These stimuli differed on two aspects from the sandpapers used in our experiments.…”
Section: Reviewing Manuscriptmentioning
confidence: 99%
“…A growing body of research shows that the information processed in one sensory modality is modulated by the simultaneous activation of other sensory modalities (see Driver & Noesselt, 2008, for a review). As a result tactile texture perception can for instance be influenced by audition (e.g., Guest et al, 2002;Jousmäki & Hari, 1998;Klatzky & Lederman, 2010;Lederman, 1979;Werner & Schiller, 1932), vision (e.g., Guest & Spence, 2003a;Guest & Spence, 2003b;Werner & Schiller, 1932), and even olfactory perception (Churchill et al, 2009;Croy, Angelo & Olausson, 2014;Demattè et al, 2006;Gonçalves et al, 2013;Kikuchi, Akita & Abe, 2013). The inter-modal interaction between touch and vision is for example shown by the fact that bimodal visual and tactile input results in superior roughness discrimination of abrasive papers (Heller, 1982), and that the visual assessment of textile roughness is less accurate in the presence of simultaneously presented incongruent tactile samples (Guest & Spence, 2003b).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A growing body of research shows that the information processed in one sensory modality is modulated by the simultaneous activation of other sensory modalities (see Driver & Noesselt, 2008 , for a review). As a result, tactile texture perception can for instance be influenced by audition (e.g., Guest et al, 2002 ; Jousmäki & Hari, 1998 ; Klatzky & Lederman, 2010 ; Lederman, 1979 ; Werner & Schiller, 1932 ), vision (e.g., Guest & Spence, 2003a ; Guest & Spence, 2003b ; Werner & Schiller, 1932 ), and even olfactory perception ( Churchill et al, 2009 ; Croy, Angelo & Olausson, 2014 ; Demattè et al, 2006 ; Gonçalves et al, 2013 ; Kikuchi, Akita & Abe, 2013 ).…”
Section: Introductionmentioning
confidence: 99%